ANALISIS SWOT DALAM MENINGKATKAN DAYA SAING PASAR TRADISIONAL DI KABUPATEN SUMBAWA - Mita Lestari; Wahyu Haryadi; Sri Rahayu (Pusat Riset dan Publikasi, 2023)
This study aims to determine the strategy in increasing the competitiveness of traditional markets in Sumbawa Regency using SWOT analysis. The type of research used in this research is descriptive with a qualitative approach. The type of data used by researchers in this study is qualitative obtained directly from research informants. The informants in this study were all parties directly involved in the management of the Brang Biji traditional market, consisting of the Head of the Cooperative and MSME Services in Sumbawa Regency, market managers and traders at the Brang Biji traditional market. The primary data used in this study was collected using a structured interview method to be studied using a SWOT analysis. The results of this study indicate that the SWOT analysis in increasing the competitiveness of the Brang Biji traditional market is in quadrant I. The strategy that can be applied in this condition is to support aggressive policies (growth oriented strategy). There are four alternative strategies generated through SWOT analysis to increase the competitiveness of the Brang Biji traditional market, namely the SO strategy which is carried out by utilizing existing strengths and opportunities, the ST strategy which is carried out by utilizing strengths to overcome the threats faced, the WO strategy which is carried out by minimizing weaknesses to be able to take advantage of opportunities, and WT strategies that are carried out by minimizing weaknesses and threats.